Ebola outbreak in West Africa, 2014 - 2016: Epidemic timeline, differential diagnoses, determining factors, and lessons for future response - Ramat Toyin Kamorudeen; Kamoru Ademola Adedokun; Ayodeji Oluwadare Olarinmoye (Elsevier, 2020)
The outbreak of Ebola virus disease (EVD) that raged between 2014 and 2016 in the West African sub-region was one of the global epidemics that spiked international public health concern in the last decade. Since the discovery of ebolavirus in 1976, the 2014-2016 epidemics have been the worst with significant case fatality rates and socioeconomic impact in the affected countries. This review looks at important health determinants that directly accounted for the spatial events of rapid spread and severity of EVD in West Africa, with consequent high fatality rates. It also brings up a time-point health determinant model to conceptualize understanding of this important outbreak with a view to enlightening the public andproviding valuable recommendations that may be crucial to preventing or curtailing any future outbreak of the disease.